PENGELOLAAN MENU BREAKFAST DI PANGERAN BEACH HOTEL PADANG - Oksavira, Alfadiya Rizki; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
One of the developing countries in Asia that is experiencing progress in the tourism sector is Indonesia. The Indonesian government's efforts to advance it are starting to improve the entire tourism sector, including hotel accommodation, tourist attractions and the culinary sector. Pangeran Beach Hotel Padang is one of the four star hotels in the city of Padang. Its strategic location is on Jl. Ir. H Juanda, Flamboyan Baru, where there are many tourist attractions and shopping centers, so this area is busy with tourists passing by. A hotel certainly has many facilities, one of which is restaurant facilities. The restaurant at the Pangeran Beach Hotel is called Mentawai Restaurant. The aim of this research is to explain the management pattern of the typical Prince Beach Hotel Padang breakfast menu. This research uses a qualitative method with a descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The results of this research are that in managing the breakfast menu, there are several important indicators that must be carried out, namely planning, organization, implementation and supervision. There are three types of breakfast menu served in Mentawai restaurants, namely Continental breakfast, Western breakfast and Indonesian breakfast so there are many variations of food served. The presentation or service carried out at this restaurant is self service, guests are invited to take their own food and drinks. The conclusion that can be drawn from this research is that menu management is an activity of planning, compiling and processing a breakfast menu in a hotel. Breakfast menu management plays a very important role in increasing guest interest and satisfaction. Keywords: Management, Menu, Pangeran Beach Hotel Padang